Upper-ocean turbulence structure and ocean-ice drag coefficient estimates using an ascending microstructure profiler during the MOSAiC drift - Fer, Ilker; Baumann, Till Martin; Koenig, Zoe Charlotte; Muilwijk, Morven; Tippenhauer, Sandra (Journal of Geophysical Research: Oceans, 2022)
Sea ice mediates the transfer of momentum, heat, and gas between the atmosphere and ocean. However, the under-ice boundary layer is not sufficiently constrained by observations. During the Multidisciplinary drifting Observatory for the Study of the Arctic Climate (MOSAiC), we collected profiles in the upper 50-80 m using a new ascending vertical microstructure profiler, resolving the turbulent structure within 1 m to the ice. We analyzed 167 dissipation rate profiles collected between February and mid-September 2020, from 89°N to 79°30′N through the Amundsen Basin, Nansen Basin, Yermak Plateau, and Fram Strait. Measurements covered a broad range of forcing (0–15 m s−1 wind and 0–0.4 m s−1 drift speeds) and sea ice conditions (pack ice, thin ice, and leads). Dissipation rates varied by over 4 orders of magnitude from 10−9 W kg−1 below 40 m to above 10−5 W kg−1 at 1 m. Following wind events, layers with dissipation urn:x-wiley:21699275:media:jgrc25172:jgrc25172-math-0001 W kg−1 extended down to 20 m depth under pack ice. In leads in the central Arctic, turbulence was enhanced 2 to 10 times relative to thin ice profiles. Under-ice dissipation profiles allowed us to estimate the boundary layer thickness (4±2 m), and the friction velocity (1–15 mm s−1, 4.7 mm s−1 on average). A representative range of drag coefficient for the MOSAiC sampling site was estimated to (4–6) × 10−3, which is a typical value for Arctic floe observations. The average ratio of drift speed to wind speed was close to the free-drift ratio of 2% with no clear seasonal or regional variability. publishedVersion